Assessment of Water Quality Status in Bondet Estuary, Cirebon - Wahyuningsih, Sri (Tomini Journal of Aquatic Science, 2021)
The coast is a water area that gets a lot of environmental pressure from human anthropogenic activities. As a result, many coastal areas are in a polluted condition, is no exception Bondet Estuary. An assessment of the condition and status of water quality needs to be carried out, as an effort to conserve coastal resources. This research aims to know the condition of water quality and determine the water quality status of the Bondet Estuary using the STORET method and the pollution index (IP). This study used survey method, where the determination of the sampling location is based on the purposive sampling method. Based on the STORET method, the water quality status of the Muara Sungai Bondet was moderately polluted with a score of -14 to -18, while the results of the assessment with the pollution index showed that it was lightly polluted with a value of 2.54 - 4.05. Several parameters that contribute to the condition of water quality degradation are salinity, TSS, and Pb. Based on these results, a sustainable management plan for the Bondet Estuary area is needed to reduce the negative impact on the environment due to various human activities.